Food Antimicrobials Nanocarriers - Adriana Blanco-Padilla; Karen M. Soto; Montserrat Hernández Iturriaga; Sandra Mendoza (The Scientific World Journal)
Natural food antimicrobials are bioactive compounds that inhibit the growth of microorganisms involved in food spoilage or food-borne illness. However, stability issues result in degradation and loss of antimicrobial activity. Nanoencapsulation allows protection of antimicrobial food agents from unfavorable environmental conditions and incompatibilities. Encapsulation of food antimicrobials control delivery increasing the concentration of the antimicrobials in specific areas and the improvement of passive cellular absorption mechanisms resulted in higher antimicrobial activity. This paper reviews the present state of the art of the nanostructures used as food antimicrobial carriers including nanoemulsions, nanoliposomes, nanoparticles, and nanofibers.